Editorial: Freedom of Expression and the Online Abyss - Maria Elliot; Kristoffer Holt (Media and Communication, 2020)
This introduction to the thematic issue Freedom of Expression, Democratic Discourse and the Social Media discusses the state of the debate surrounding freedom of expression in the field of communication studies and presents four original articles dealing with freedom of speech in contemporary media from different perspectives.